2014
DOI: 10.1111/appy.12155
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder among female victims of sexual assault in China: prevalence and psychosocial factors

Abstract: These findings suggest that negative coping bias and neuroticism were predisposing risk factors that increase PTSD symptoms, while objective support, subjective support, support utilization, and positive coping style were protective factors for PTSD following sexual assault, and provide prima facie evidence for posttrauma intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Oriental culture is relatively conservative (60), and Chinese traditional culture emphasizes female chastity (61). Females victimized by child sexual abuse may internalize the social stigmatization of "victim of sexual abuse" and suffer from a burning sense of shame and self-denial (62). Besides, some female participants in our study may be reluctant to reveal their experiences of sexual abuse, which may lead to an underestimation of the association between sexual abuse and depressive symptoms among females.…”
Section: Discussionmentioning
confidence: 91%
“…Oriental culture is relatively conservative (60), and Chinese traditional culture emphasizes female chastity (61). Females victimized by child sexual abuse may internalize the social stigmatization of "victim of sexual abuse" and suffer from a burning sense of shame and self-denial (62). Besides, some female participants in our study may be reluctant to reveal their experiences of sexual abuse, which may lead to an underestimation of the association between sexual abuse and depressive symptoms among females.…”
Section: Discussionmentioning
confidence: 91%
“…A few studies have been conducted on Chinese populations with mixed findings noted. A study conducted in Mainland China found that one of seven female IPSV survivors suffered from posttraumatic stress disorder (PTSD) (Sui et al, 2014) and another noted that IPSV significantly predicted PTSD and depressive symptoms (Tiwari et al, 2014). However, Chan et al (2008) found no significant association between IPSV and suicidal ideation, self-harm and depression in his study of Chinese university students.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis with mixed trauma samples indicated that 26.2% of subthreshold PTSD eventually develop into full PTSD [ 4 ]. The prevalence of PTSD including subthreshold PTSD in China is similar to that in other regions, ranging from 13.0% to 37.8% depending on different trauma types [ 5 , 6 ]. Considering the large population and limited resources for mental health, an easy and cost-efficient PTSD treatment is of urgent need.…”
Section: Introductionmentioning
confidence: 79%